(untitled) (Вестник КазНУ. Серия Востоковедения, 2017)
No matter what form of speech it is (oral or written) the role of punctuation in any language is important as it is aimed at transforming the meaning of a text. The given article deals with the comparative analysis of punctuation of the Chinese and Kazakh languages. Сomparative analysis of punctuation of the Chinese and Kazakh languages will make the process of language acquisition easier and learn features of structure of language.